The Significance of Dementia with Functional Balance in The Elderly - Wardhani, Riska Risty; Rahmawati, Marisa Dwi (Annual Physiotherapy Scientific Meeting Proceeding, 2022)
Introduction: Dementia is a progressive impairment of global cognitive function. The most serious problem during the aging process is the decline in cognitive function, which makes it difficult for the elderly to live independently and increases the risk of dementia. As a result, the elderly will suffer from behavioral disorders and a lower quality of life. Dementia can affect balance in the elderly. This study aims to determine the relationship between dementia and balance disorders in the elderly. Methodology: This study employed the Cross-Sectional method. The number of respondents were 50 elderly people aged 60 years and over. The sampling technique used was purposive sampling. The research instruments used were the Mini Mental Status Exam (MMSE) and the Berg Balance Scale (BBS). The data was analyzed by using the Kendall Tau test. Research findings: The results of this study indicate that there is a relationship between dementia and functional balance in the elderly, with a p-value of 0.046 and a correlation coefficient of 0.212, indicating a weak relationship. Conclusions: There is a weak relationship between dementia and balance disorders in the elderly.